Development of Electronic LKPD Based on Project-Based Learning (PjBL) Integrated STEM on Reaction Rate Material For Phase F - Halimatuzzahra Halimatuzzahra; Isana Supiah Yosephine Louise (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
This development research aims to analyze the characteristics, feasibility, practicality, and readability of electronic student worksheet based on Project-Based Learning (PjBL) integrated STEM on reaction rate material for phase F. This research uses the stages of the 4-D model consisting of the Define, Design, Develop, and Disseminate stages. The instruments used to collect data consist of electronic student worksheet feasibility sheets, electronic student worksheet practicality sheets, electronic student worksheet readability sheets, and teacher and learner needs analysis sheets. The results of this study indicate that the characteristics of electronic student worksheet developed can be operated via Android smartphones and laptops, have been adapted to the syntax of the STEM integrated PjBL model, can be used anytime and anywhere, prioritize the demands of using technology in learning, and help reduce the use of paper during the learning process. Electronic student worksheet based on Project Learning (PjBL) integrated STEM on reaction rate material obtained an average feasibility score of 134.5 (very good), practicality of 117.5 (very good), and readability of 66.27 (very good). This means that the electronic worksheets based on Project-Based Learning (PjBL) integrated with STEM on the topic of reaction rates developed can be deemed suitable for use in learning. The implication for the research is that electronic worksheets based on Project-Based Learning (PjBL) integrated STEM on the topic of reaction rates are recommended for use as one of the learning resources used by teachers to make learning more meaningful.